Circulating oncometabolite D-2-hydroxyglutarate enantiomer is a surrogate marker of isocitrate dehydrogenase–mutated intrahepatic cholangiocarcinomas. (February 2018) - Delahousse, Julia; Verlingue, Loic; Broutin, Sophie; Legoupil, Clémence; Touat, Mehdi; Doucet, Ludovic; Ammari, Samy; Lacroix, Ludovic; Ducreux, Michel; Scoazec, Jean-Yves; Malka, David; Paci, Angelo; et al.
Abstract: Therapeutic resources are limited for advanced biliary tract cancers and prognosis remains poor. Somatic mutations in isocitrate dehydrogenase (IDH)1/2 gene are found in 5–36% of patients with intrahepatic cholangiocarcinoma (ICC). The mutant forms of IDH1/2 catalyse the non-reversible accumulation of 2-hydroxyglutarate (2HG). Increasing numbers of indirect or direct-targeted therapies are developed to IDH1/2 mutations and could be assisted by a routinely feasible, rapid and inexpensive serum 2HG measurement by liquid chromatography coupled to tandem mass spectrometry. By comparing eight patients with an IDH1/2 -mutated ICC to nine patients with wild-type IDH1/2 ICC, we found significantly higher levels of 2HG in patients with IDH1/2 mutations versus the wild-type group (median, 10.9 vs. 0.8 μmol/L, p = 0.0037). D and L-2HG enantiomer levels significantly differed between the two groups with a higher level of D-2HG (p < 0.0001) in patients with IDH1/2 mutations. Accordingly, the D/L ratio was markedly higher in the patients with IDH1/2 mutations compared with the wild-type group (38.0 vs. 0.9 μmol/L, p < 0.0001). D-2HG measurement ensured 100% sensitivity and specificity at a cut-off of 0.6 μmol/L. D-2HG levels were correlated with tumour burden and tumour response to treatment with IDH-targeted therapies or indirect therapies. D-2HG serum level measurement by liquid chromatography coupled to tandem mass spectrometry is a sensitive, specific, precise (a coefficient of variation <10% and an accuracy >95%), fast (9 min run per sample) and inexpensive surrogate marker of IDH1/2 somatic mutation in ICC. Systematic measurement in patients with ICC may facilitate access to, and monitoring of, IDH-driven therapies. Highlights: Somatic mutations in isocitrate dehydrogenase ( IDH ) are found in patients with intrahepatic cholangiocarcinoma. Production of D-2-hydroxyglutarate enantiomers (2HG) is increased in the serum of patient with IDH mutation. D-2HG measurement and D/L-2HG ratio are a reproducible and quick tools to predict the IDH mutation. Systematic measurement may facilitate access to IDH-driven therapies. D-2HG measurement and D/L-2HG ratio are a tool for monitoring treatment.